Improving the Quality of Graduates in Maintaining the Existence of Islamic Boarding Schools - Zahrotul Luqmi, Fitra; Patimah, Siti (Jurnal Multidisiplin Indonesia, 2023)
The purpose of this study is to describe planning, organizing, achieving and evaluating based on improving the quality of the quality of student graduates in maintaining the existence of pesantren that have been implemented at Madrasah Aliyah Wali Songo Putri under the auspices of Pondok Pesantren "Wali Songo" Ngabar. This research is a descriptive qualitative research that describes the improvement of the quality of the quality of student graduates. The conclusion of the results of this study is a description of improving the quality of the quality of graduates of students in maintaining the existence of pesantren by paying attention to: a) Planning to improve the quality of the quality of graduates by implementing an annual work program that involves educational institutions in achieving educational goals in accordance with a predetermined program by maintaining the existence of pesantren values, b) Organizing to improve the quality of the quality of graduates in maintaining the existence of pesantren, namely by managing good resources, c) Achievement of improving the quality of the quality of graduates in maintaining the existence of pesantren, namely by looking at the results of institutional accreditation, d) Evaluation of improving the quality of the quality of graduates in maintaining the existence of pesantren, namely the need for adjustments between school programs to improve the quality of the quality of graduates and the pesantren service system that has been determined by continuing to run to maintain the existence of pesantren in the scope of society